Subtracting 6 from each of

5x=6=10 yields

5x=4.Dividing both sides of

5x=4 by 5 yields

x=.The value of x can now be substituted into the expression

10x+3,giving

10()+3=11 Alternatively, the expression

10+x can be rewritten as

2(5x+6)−9, and 10 can be substituted for

5x+6 giving

2(10)−9=11Choic A,B and D are incorrect. Each of these choices leads to

5x+6≠10 contradicting the given equation,

5x+6=10, For example, choice A is incorrect because if the value of

10x+3 were 4, then it would follow that x = 0.1, and the value of

5x+6 would be 6.5, not 10.